2017
DOI: 10.1371/journal.pone.0182134
|View full text |Cite
|
Sign up to set email alerts
|

Regional citrate anticoagulation for continuous renal replacement therapy in pediatric patients with liver failure

Abstract: Pediatric liver failure patients frequently develop multiple organ failure and require continuous renal replacement therapy (CRRT) as part of supportive therapy in the pediatric intensive care unit. While many centers employ no anticoagulation for fear of bleeding complications, balanced coagulation disturbance predisposes these patients to clotting as well as bleeding, making maintenance of longer circuit life to deliver adequate dialysis clearance challenging. Regional citrate anticoagulation (RCA) is an att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 33 publications
4
23
4
1
Order By: Relevance
“…RCA is often needed in newborns and infants due to postoperative status or coagulopathy and was used in 56% of circuits in the pediatric CRRT registry . Despite growing knowledge and experience in performing CRRT with RCA in the pediatric population, RCA in newborns and infants remains challenging, mainly due to relative overdosing of citrate (imbalance between blood flow and BW), which increases the risk of citrate accumulation. Unfortunately, even the newly developed devices, designed specifically for infants (eg, CARPEDIEM and NIDUS systems), do not yet provide automated RCA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RCA is often needed in newborns and infants due to postoperative status or coagulopathy and was used in 56% of circuits in the pediatric CRRT registry . Despite growing knowledge and experience in performing CRRT with RCA in the pediatric population, RCA in newborns and infants remains challenging, mainly due to relative overdosing of citrate (imbalance between blood flow and BW), which increases the risk of citrate accumulation. Unfortunately, even the newly developed devices, designed specifically for infants (eg, CARPEDIEM and NIDUS systems), do not yet provide automated RCA.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, even the newly developed devices, designed specifically for infants (eg, CARPEDIEM and NIDUS systems), do not yet provide automated RCA. To our best knowledge, only a few studies have reported detailed data on performance of RCA during CRRT in newborns and infants and further reporting on citrate use has been recommended in a recent review …”
Section: Introductionmentioning
confidence: 99%
“…Systemic anticoagulation with heparin risks disrupting the balanced coagulation defects was seen in LF toward severe bleeding, while insufficient anticoagulation can disrupt circuit life due to thrombosis and potentiate systemic inflammation [12,21]. Citrate metabolism occurs not only in the liver, but also in the kidneys, intestines, and skeletal muscle as well with evidence of safe and effective use in the LF population continuing to emerge [8,12,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…We choose RCA as our primary anticoagulation for ELS and CRRT. We have previously published safety and efficacy data regarding RCA for CRRT in pediatric LF [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation